Service-Oriented Architecture for Cloud Application Development - Benfenatki, Hind; Kemp, Gavin; Ferreira da Silva, C.; Benharkat, Aïcha-Nabila; Ghodous, P. (Proc. of the 21st ISPE International Conference on Concurrent Engineering (CE 2014), Advances in Transdisciplinary Engineering, Vol. 1: Moving Integrated Product Development to Service Clouds in Global Economy, 2014)
Software engineering used several approaches for the development of application such as service oriented approaches. Nowadays, with the advent of cloud computing and the convergence toward “Everything as a Service”, application development is moving to a new paradigm, abstracting the underlying architecture and infrastructure. The literature does provide some work describing frameworks and architectures for cloud software development, but not one that covers the whole application development lifecycle. Furthermore, these papers are mainly dedicated to developers and do not provide a business stakeholder a method or an easy to use service to deploy their business application without the help of an IT-professional. Our work fits into the perspective of defining a Service- Oriented Architecture for Cloud Application Development. The architecture we propose is designed for non-IT professional users. It avoids the huge technical background needed for cloud application development by automating the process of development; avoids PaaS dependency and advocates the implicit collaboration by reusing and composing services. This article will give a proposed architecture for this objective as well as an example of its implementation.